The Natorp's reception by the students of the JAE (1906-1916): republican revisionism of socialism, political and educational elitism and comprehensive school - Carlos Martínez Valle (FahrenHouse, 2018)
The article explores the conditions of possibility and political and educational uses of the reception of Paul Gerhard Natorp between 1906 and 1916 by his Spanish students. The article analyzes the ideas that were rejected in possible intellectual alternatives such as John Dewey: naturalism, socially defined morality and radical participatory democracy. These ideas impeded spiritualism, which they consider a requisite for regeneration directed by the elites. Neo-idealism rejected conservatism, and individualism, liberalism and positivism. His gnoseology defended a transcendent organicism and the superiority of philosophy as a normative science that united natural and moral laws. These ideas allowed them to reformulate a republican-reformist ideology, which they call «socialist liberalism». These ideas granted them a directive role as the philosophical elites and allowed them to carry out a republican revision of socialism. Natorp also provides them with a «religion of humanity» and social education, which allow them to justify the direction of the regeneration of the country by the bourgeois reformist elites and attack the Church and its educational power, which was in line with the program of the Einheitschule. The students of the JAE didn't received Natorp for supporting the comprehensive school, as his gnoseology and pedagogy justified the role of a leading intellectual elite separated from the teachers, and an academic pedagogy that reinforced social reproduction by preventing educational democracy.